Comparison between water flosser and regular floss in the efficacy of plaque removal in patients after single use - Hoda Abdellatif; Nassreen Alnaeimi; Hessah Alruwais; Rawan Aldajan; Mamata Iranna Hebbal (Saudi Dental Journal)
Objective: The objective was to compare water flosser and regular floss in the efficacy of plaque removal in patients after single use. Materials and Methods: A randomized controlled clinical trial was conducted to compare the plaque removal efficacy of water flosser and regular floss. Eighty three subjects who met the inclusion criteria were recruited from dental clinic. Silness and Löe plaque index was measured for all the subjects prior to and after the intervention by an examiner who was blind to the type of aid used. The type of floss used was randomly assigned to each side of the oral cavity; unflavored waxed regular floss (oral B) used on one side, while a water flosser (Waterpik® Cordless Plus Water Flosser) was used on the other side. A trained investigator used either unflavored waxed regular floss or water flosser as assigned. Paired t-test was used to compare between the two groups. Results: The mean plaque scores at baseline were 1.10(±0.38) and 0.94(±0.38) respectively for regular floss and water flosser. The mean plaque scores were 0.12(±0.13) and 0.12(±0.15) respectively for regular floss and water flosser. There was no statistically significant difference in the plaque scores (p = 0.58) between the groups after the use of respective interdental aids. There was a statistically significant difference in the plaque scores before and after use of interdental aids for both the groups (p < 0.001). Reduction in plaque scores for regular floss and water flosser groups was 89.09% and 87.23% respectively. Conclusion: The results showed that water flosser was as efficient as regular floss in removing interdental plaque on single use. Water flosser could be recommended for subjects lacking manual dexterity, by care takers for better plaque control and subjects with fixed prostheses or undergoing orthodontic treatment.